Paeoniflorin Attenuated Oxidative Stress in Rat COPD Model Induced by Cigarette Smoke. (28th November 2016) - Lin, Jinpei; Xu, Fei; Wang, Genfa; Kong, Lingwen; Luo, Qingli; Lv, Yvbao; Liu, Jiaqi; Wei, Ying; Li, Lulu; Zhang, Hongying; Dong, Jingcheng
Abstract : Paeoniflorin (PF), a monoterpene glucoside, might have an effect on the oxidative stress. However, the mechanism is still unknown. In this study, we made the COPD model in Sprague-Dawley (SD) rats by exposing them to the smoke of 20 cigarettes for 1 hour/day and 6 days/week, for 12 weeks, 24 weeks, or 36 weeks. Our findings suggested that smoke inhalation can trigger the oxidative stress from the very beginning. A 24-week treatment of PF especially in the dosage of 40 mg/kg·d can attenuate oxygen stress by partially quenching reactive oxygen species (ROS) and upregulating antioxidant enzymes via an Nrf2-dependent mechanism.